(untitled) (Fiep Bulletin - online, 2016)
This study aimed to investigate through a systematic review, the influence of exercise on depressive symptoms among elderly people. Original and review articles related to the topic, published in English and Portuguese, published between 2003 and 2014 selected in the databases SciELO, PubMed, Science Direct and BIREME, using using four sets of intersecting terms of bibliographic search, elderly, physical activity, exercise and depression. The results found through research made it possible to locate 75 articles on the thematic studied, 10 of them revisions and 2 monographs. In the end, 14 articles of original studies were included in this study, analyzed and entered into a table. The results found in studies found that 100% of the studies had positive responses regarding the influence of physical exercise on the improvement of the depressive state of elderly. We can conclude according to the results shown in this review, that physical exercise contributes significantly in reducing depressive symptoms in the elderly and in reducing scores for depression, and the regular physical exercises helps in preserving mental health the elderly.